Analysis of the profitability of the Spanish business sector with investment presence in China. Issue 2 (13th May 2014) - Marin-Anglada, Quico; Campa-Planas, Fernando; Beatriz Hernandez-Lara, Ana
Abstract : Purpose: – This article aims to compare the average profitability by sector for companies that have invested in China during 2008-2011, with the average profitability for Spanish firms from the same sector. Design/methodology/approach: – Analysis done through Analysis System of Iberian Balances (SABI) database. Findings: – The results show that companies that invest in China gain economic rewards that are greater than those that do not invest in China, with the most profitable sectors comparatively being the metallurgy and the wholesale trade. Originality/value: – We have not found previous analysis in this way.